Ethnobotanical study of medicinal plant uses in polycystic ovary syndrome in western of Algeria - Messaoud, Amira; Ouali, Siheme; Belkacem, Anfal; Harir, Noria; Zahzeh, Meriem Rabia; Drici, Amine El Mokhtar; Benmessaoud, Amina; Elmezouar, Wassila Nesrine; Zemri, Khalida (Ethnobotany Research and Applications, 2026)
Background: Polycystic ovary syndrome (PCOS) is a common endocrine-metabolic disorder in women of reproductive age. In many communities, medicinal plants are used to manage menstrual irregularities, hyperandrogenic symptoms and metabolic complications, yet this knowledge remains poorly documented in western Algeria. This study aimed to document and quantitatively assess medicinal plants used for PCOS management in western Algeria. Methods: From March to July 2024, we conducted a cross-sectional ethnobotanical survey in five provinces of western Algeria using semi-structured interviews with 150 informants (women with PCOS, traditional healers, herbalists and herb sellers). Plant specimens were collected during field visits and/or purchased from local markets as reported by informants, identified using standard taxonomic procedures, and voucher specimens were deposited in the herbarium of Djillali Liabes University of Sidi Bel Abbes. Use reports were analysed using relative frequency of citation (RFC), use value (UV), informant consensus factor (ICF) and fidelity level (FL). Results: We recorded 27 medicinal plant species belonging to 17 families. Lamiaceae (five species) and Apiaceae (four species) were the most represented families. Atriplex halimus L. showed the highest cultural prominence (RFC=0.5266; UV=0.0266), followed by Salvia officinalis L. (RFC=0.3400; UV=0.0333). Most remedies were prepared as infusions or decoctions and administered orally. High agreement among informants was observed for menstrual and hormonal disorders (ICF=0.94). Conclusion: This first quantitative ethnobotanical report on PCOS remedies in western Algeria highlights a small set of culturally salient species that warrant pharmacological and safety evaluation. The documented knowledge may support future development of affordable complementary approaches and conservation of local ethnomedicinal heritage. Keywords: Ethnobotanical Survey; Medicinal Plants; Polycystic Ovary Syndrome; Traditional Medicine; Western Algeria